2015
DOI: 10.1111/anae.13206
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the i‐gel and the PRO‐Breathe® laryngeal mask during pressure support ventilation in children

Abstract: SummaryMany studies comparing the i-gel TM with laryngeal masks include patients in whom laryngeal mask cuff inflation pressures are higher than recommended, or involve the use of neuromuscular blocking drugs and positive pressure ventilation. We compared the i-gel with the PRO-Breathe â laryngeal mask in anaesthetised, spontaneously breathing children. Two hundred patients aged up to 16 years were randomly allocated to either the i-gel or the PRO-Breathe laryngeal mask. The PRO-Breathe was inflated to an intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The full texts of 118 articles were examined in detail. We included 65 articles in this network meta‐analysis (Fig. ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The full texts of 118 articles were examined in detail. We included 65 articles in this network meta‐analysis (Fig. ).…”
Section: Resultsmentioning
confidence: 99%
“…The trials had a median (range [IQR]) sample size of 60 (27–240 [53–100]). Sevoflurane was administered for anaesthesia induction in 44 studies . There were eight crossover designed studies .…”
Section: Resultsmentioning
confidence: 99%
“…The paediatric i‐gel has the same design as the adult device and has potential to cause less postoperative sore throat because there is no cuff inflation. The i‐gel has been compared with the ProSeal LMA laryngeal mask, the LMA laryngeal mask Classic , the LMA laryngeal mask Supreme and the PRO‐Breathe ® silicone disposable SAD (Well Lead Medical Co Ltd, Panyu, China) in both spontaneously breathing and patients who received neuromuscular blockers, but these studies were not sufficiently powered to detect a difference in complication rates. However, Smith and Bailey found that there was no difference in the overall incidence of postoperative sore throat between the i‐gel and different SADs when data were pooled.…”
Section: Methodsmentioning
confidence: 99%
“…However one study by Drake-Brockman et al 24 found the PRO-Breathe LMA superior to i-gel LMA in a wide age range of children (0–16 years) with LMA size range of 1.5–3. A study by Lee et al 25 in a lower age range of infants (10 months–5 years) found the Classic LMA had similar leak pressure to the i-gel LMA but longer insertion time.…”
Section: Discussionmentioning
confidence: 97%